140 років Емському указу: у сприйнятті сучасників та оцінках істориків - Реєнт, О. (Краєзнавство, 2016)
Розкрито особливості сприйняття Емського указу українською громадськістю останньої чверті ХІХ ст., висвітлено оцінки істориків дорадянського та радянського періодів щодо впливу Указу 1876 р. на розвиток української культури, національний рух в українських губерніях Російської імперії. Раскрыты особенности восприятия Эмского указа украинской общественностью последней четверти XIX в., показаны оценки историков досоветского и советского периодов относи- тельно влиянию Указа 1876 года на развитие украинской культуры, национальное движение в украинских губерниях Российской империи. The weakening of anti-Ukrainian censorship in the early 1870-ies gave a new impetus to the development of Ukrainian studies and new impetus to Ukrainian book publishing in general. It contributed to the further content development of the "Ukrainian question." In the first half of 1870 Kyiv became the real center of Ukrainian multi-faceted book publishing. In the 1870-ies several new publishing and lithograph houses appeared in Ukrainian county towns. It indicated the growth of Ukrainian book publishing. The Ems decree which entered into force in 1876 made it impossible to implement the plans of the representatives of nationally conscious intelligentsia to publish in the Ukrainian language. Unable to legally protest against this act of censorship, the most active intelligentsia representatives were still looking for the ways to convey to the government their disagreement with the decision of the imperial power. However, any discussion of the Ems decree on the pages of periodicals in the Russian Empire was not possible. The lack of accurate and true information about the content of the royal decree, which was signed in Ems in 1876, mislead the representatives of Ukrainian intelligentsia about the true motives of banning Ukrainian theater performances, of persecuting nationally conscious Ukrainian teachers and of removing Ukrainian books from libraries. The embodiment of the Ems decree in the activities of Rus - sian Empire censorship bodies was called by the contemporaries "the period of dead years" in the Ukrainian book publishing. It negatively impacted the solution of the "Ukrainian question" in the future. Deterring the growth of the Ukrainian movement, it still contributed to the activation of latent forms of protest by the most conscious Ukrainians. Moreover, it gave an impetus to the development of Ukrainian-oriented periodicals in Galicia. However, the implementation of the restrictive act caused a lot of legal conflicts and oddities in the imperial censorship, police and administration bodies. All this is reflected negatively in the complex, including the image of the government in the public eye, exacerbating the confrontation between the autocracy and progressive intellectuals, increasing the ranks of the opposition-minded representatives.